Self-insurance, self-protection, and increased risk aversion: An intertemporal reinvestigation - Annette Hofmann; Richard Peter (Hamburg University, Institute for Risk and Insurance, 2012)
This paper studies the effect of increased risk aversion on self-insurance and self-protection in a two-period framework. Here risk management incentives and consumption smoothing incentives are traded off, and the monotonic relationship between self-insurance and risk aversion may no longer hold as more risk-averse agents cannot always afford spending more on self-insurance. A very similar relationship holds for self-protection making self-insurance and self-protection much more alike in a two-period model. We also extend the model to a joint analysis of self-insurance/self-protection and saving decisions.
Keywords: 330; self-insurance; self-protection; risk aversion; time structure